2014
DOI: 10.1111/jfb.12440
|View full text |Cite
|
Sign up to set email alerts
|

Description of a new cryptic, shallow‐water tonguefish (Pleuronectiformes: Cynoglossidae:Symphurus) from the western North Pacific Ocean

Abstract: Combined results based on morphological characters and analyses of partial sequences of the 16s rRNA and coI genes confirm the validity of a new, cryptic, symphurine tonguefish from the western North Pacific Ocean. Symphurus leucochilus n. sp., a diminutive species reaching sizes to c. 67 mm standard length, is described from nine specimens that were collected from fish-landing ports and from trawls made at c. 150 m off Taiwan and Japan. Symphurus leucochilus shares many similar features with those of Symphuru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 37 publications
2
18
0
Order By: Relevance
“…The mtDNA 16S rRNA gene primers were sensitive and successfully amplified the targeted DNA fragments for each species. Similar 16S regions generated fragments by the same primer pair in other species have been reported (Lee et al, 2014;Quraishi et al, 2015;Carvalho et al, 2004).…”
Section: Table 3 Pair Wise Genetic Distance Involving 11 Nucleotide Sequences (7 Investigatedsupporting
confidence: 82%
“…The mtDNA 16S rRNA gene primers were sensitive and successfully amplified the targeted DNA fragments for each species. Similar 16S regions generated fragments by the same primer pair in other species have been reported (Lee et al, 2014;Quraishi et al, 2015;Carvalho et al, 2004).…”
Section: Table 3 Pair Wise Genetic Distance Involving 11 Nucleotide Sequences (7 Investigatedsupporting
confidence: 82%
“…They considered S. microrhynchus to be a widespread species, but new data (see below) reveals that at least five other species were included in their account for S. microrhynchus. Lee et al (2014; also confirmed that more than a single species was present among material identified as S. microrhynchus in Munroe & Marsh (1997). In fact, among specimens examined by Munroe & Marsh (1997), approximately six nominal species (including S. holothuriae) were included.…”
Section: Species Accounts For Members Of the S Microrhynchus Species Complex With Low Scale Countssupporting
confidence: 61%
“…Approximately 31 nominal species of Symphurus are distributed in the Indo-Pacific region, most of which are deepwater species (Alcock 1891;Norman 1939;Chabanaud 1955a;Munroe 1992;Krabbenhoft & Munroe 2003;Munroe & Hashimoto 2008;Lee et al 2009a;2009b;Munroe et al 2011;Lee et al 2013;2014). Among species of Symphurus reported from the Indo-Pacific region, only five have been recorded from depths shallower than 200 m. This assemblage of shallow-water species of Symphurus comprises four characterized by having 12 caudal-fin rays: S. microrhynchus (Weber, 1913), the first described species of shallow-water tonguefish reported from the Indo-West Pacific region (Weber 1913;Chabanaud 1955b;Munroe & Marsh 1997;Lee et al 2013;2014;; S. holothuriae Chabanaud, 1948, a species collected off western Australia and known only from the holotype, and considered a possible junior synonym of S. microrhynchus (Weber, 1913) by Chabanaud (1955b) and regarded as a junior synonym of S. microrhynchus by Munroe & Marsh (1997); S. leucochilus Lee et al 2014, a species formerly frequently misidentified as S. orientalis (Bleeker, 1879) and one with meristic features that overlap those of S. microrhynchus and related species (Lee et al 2014;; and S. longirostris Lee et al 2017, a species recently described from Japanese waters whose meristic features are similar to, or overlap those of, S. microrhynchus and related species. Among Indo-Pacific Symphurus, 14 nominal species, including five nominal species described in this study, have 12 caudal-fin rays (Alcock 1891;Chabanaud 1948;1955b;1957;Munroe & Marsh 1997;Munroe 2001;Lee et al 2013;2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations